Anticancer activity of osmium(VI) nitrido complexes in patient-derived glioblastoma initiating cells and in vivo mouse models. (1st March 2018) - Berger, Gilles; Grauwet, Korneel; Zhang, Hong; Hussey, Amanda M.; Nowicki, Michal O.; Wang, David I.; Chiocca, E. Antonio; Lawler, Sean E.; Lippard, Stephen J.
Abstract: Glioblastoma is the most prevalent and lethal primary intrinsic brain tumor with a median patient survival of less than two years, even with the optimal standard of care, namely, surgical resection followed by radiotherapy with adjuvant temozolomide chemotherapy. Long-term survival is extremely rare and there is a tremendous need for novel GBM therapies. Following our prior reports on the anticancer activity of osmium(VI) nitrido compounds and their effectiveness against cancer initiating cells, we investigated the efficacy of Os(VI) on GBM initiating cells in vitro and in vivo . Conventional MTT and 3D cytotoxicity assays revealed that patient-derived GBM models were sensitive to cisplatin, TMZ, and two Os(IV) derivatives. Rapid cell death occurred at low micromolar concentrations of the Os(IV) compounds. Cell cycle analysis, Os uptake studies, and cellular distribution experiments provided further insight into the anticancer properties of these compounds, indicating differential uptake for both compounds and a modest G2 /M arrest after treatment. Moreover, in vivo experiments showed a significant increase in survival after a single intracranial chemotherapeutic injection, results that warrant further studies using this approach. Highlights: Osmium(VI) nitrido complexes showed micromolar-range activity against patient-derived glioblastoma cell lines. A fluorescence-based 3D-culture assay was used to compare the osmium compounds to cisplatin and temozolomide. In vivo experiments showed a significant increase in survival following a single intracranial injection. Uptake and cellular distribution of the osmium complexes showed a better penetration with the neutral complex.